2019
DOI: 10.1111/jasp.12632
|View full text |Cite
|
Sign up to set email alerts
|

Meat on the menu? How the menu structure can stimulate vegetarian choices in restaurants

Abstract: Excessive meat consumption has a negative impact on people's health, animal welfare, and the environment in general. Remarkably, however, despite the growing number of flexitarians, only a small number of people choose a vegetarian dish at a restaurant. Therefore, in the current study, we tested how vegetarian dishes need to be presented in order to stimulate the choice for these dishes. In an online study, participants were presented with one of four different menus: Either an all vegetarian menu, an all vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Another online study revealed that approximately three of four participants make vegetarian choices when the menu includes only vegetarian dishes with extra-meat options listed at the bottom of the menu. By contrast, only about half of the participants choose vegetarian dishes when the menu lists vegetarian and meat dishes together [31]. Field studies in campus cafeterias produced similar results: when vegetarian dishes are placed at the top of the board menu, the share of sold vegetarian dishes increases [28,33].…”
Section: Menu Defaultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Another online study revealed that approximately three of four participants make vegetarian choices when the menu includes only vegetarian dishes with extra-meat options listed at the bottom of the menu. By contrast, only about half of the participants choose vegetarian dishes when the menu lists vegetarian and meat dishes together [31]. Field studies in campus cafeterias produced similar results: when vegetarian dishes are placed at the top of the board menu, the share of sold vegetarian dishes increases [28,33].…”
Section: Menu Defaultsmentioning
confidence: 82%
“…There are several studies in the context of health- [18,[23][24][25] and environment-related food choice [16,17,[23][24][25][26][27] in which the examined labels combined these two types of nudging. In other studies, default and non-default dishes were varied systematically on menus or board menus [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This study is one of first interventional trials in China and to the authors' knowledge in Asia that uses behavioral insights and nudge theories to promote customers' online ordering behaviors towards salt reduction. Existing similar studies are mostly conducted in western countries, e.g., Canada [26], Australia [15], the United Kingdom [13][14][15][16][17][18], and the United States [14]. Given that western cuisines and taste preferences are different from those in Asia, our study may contribute to the body of references for other Asian countries with similar cooking and eating practices.…”
Section: Expected Outcome and Potential Impactmentioning
confidence: 94%
“…A few studies have applied nudges to affect consumers food choices. In these studies, researchers deployed intervention strategies, such as position nudge in menu design to affect consumers' food choices and measured the outcomes by caloric intake [11][12][13][14], fat [11,13], sugar [11], sodium [11,12] or salt, fruit and vegetables [15], and vegetarian [16,17]. Most of the studies were conducted on online food ordering platforms for workplace and school canteens [11,15], rather than on commercial food ordering systems that serve the whole population.…”
Section: Review Of Existing Studiesmentioning
confidence: 99%
“…Moreover, this normative signal arises from the conference organizers, which are members of the conference goers' ingroup with status. This interpretation is bolstered by a study of food choices from hypothetical restaurant menus in the Netherlands (de Vaan et al 2019). When the menu presented vegetarian dishes as the default (meat could be optionally added to any dish), participants reported this as indicating stronger social norms to eat vegetarian at that restaurant.…”
Section: Social Meat Reductionmentioning
confidence: 99%